Identification of Potential Inhibitors of 3CL Protease of SARS-CoV-2 From ZINC Database by Molecular Docking-Based Virtual Screening - Abdusalam, Ashraf Ahmed Ali; Murugaiyah, Vikneswaran (Frontiers in Molecular Biosciences, 2020)
The rapid outbreak of Coronavirus Disease 2019 (COVID-19) that was first identified in Wuhan, China and then spread worldwide is caused by a novel severe acute respiratory syndrome coronavirus 2 (SARS CoV 2). The 3CL protease (3CLpro) is the main protease for the SARS CoV 2, which is responsible for the viral replication and therefore considered as a potential drug target since there is no specific and effective vaccine available against this virus. In this paper, we reported virtual screening (VS) and molecular docking of 2000 compounds obtained from the ZINC database and 10 FDA-approved (antiviral and anti-malaria) on 3CLpro using AutoDock Vina to find potential inhibitors. The screening results showed that the top four compounds, namely ZINC32960814, ZINC12006217, ZINC03231196 and ZINC33173588 exhibited high affinity at the 3CLpro binding pocket. Their free energy of binding (FEB) with AutoDock Vina scores were -12.3, -11.9, -11.7 and -11.2 kcal/mol while AutoDock scores were -12.61, -12.32, -12.01 and -11.92 kcal/mol, respectively. These results were better than the co-crystallized ligand N3, whereby its FEB was -7.5 kcal/mol and FDA-approved drugs. Different but stable interactions were obtained between the four identified compounds with the catalytic dyad residues of the 3CLpro. In conclusion, novel 3CLpro inhibitors from the ZINC database were successfully identified using VS and molecular docking approach, fulfilling the Lipinski rule of five, and having low FEB and functional molecular interactions with the target protein. The findings suggest that the identified compounds may serve as potential leads that act as COVID-19 3CLpro inhibitors, worthy for further evaluation and development.